2019
DOI: 10.1177/0165551519890515
|View full text |Cite
|
Sign up to set email alerts
|

Group trip planning and information seeking behaviours by mobile social media users: A study of tourists in Australia, Bangladesh and China

Abstract: Social media plays an increasingly important role in travel information seeking and decision-making. However, there is limited understanding of how a group of tourists use social media to plan trips collaboratively and the different practices between countries. In this study, we investigated the collaborative information seeking (CIS) and sharing behaviours of mobile social media users from Australia, Bangladesh and China. Specifically, we surveyed a total of 219 participants to explore the differences in CIS … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 51 publications
0
4
0
Order By: Relevance
“…'Social networks promote information transmission' [111], help actors access information in a broader context, and improve the quality, relevance and timeliness of information [112]. Social interactions are considered as an important complement of and are interwoven with in-group collaborative tourism information seeking [113]. To ¨tterman and Wide ´n-Wulff [114] found that cultural differences and social norms are barriers to information sharing between university professors.…”
Section: Social Capitalmentioning
confidence: 99%
“…'Social networks promote information transmission' [111], help actors access information in a broader context, and improve the quality, relevance and timeliness of information [112]. Social interactions are considered as an important complement of and are interwoven with in-group collaborative tourism information seeking [113]. To ¨tterman and Wide ´n-Wulff [114] found that cultural differences and social norms are barriers to information sharing between university professors.…”
Section: Social Capitalmentioning
confidence: 99%
“…Tourists make pre-tour plans including when to visit, how long to spend and how to get there (Fardous et al , 2019). In this study, tour plans included tour time (date and duration), tour companions and means of transportation.…”
Section: Resultsmentioning
confidence: 99%
“…According to an empirical study of mobile social media users in China, approximately 46% (626 million) of Chinese people use social media actively every day to meet various demands [22]. Therefore, this research uses online questionnaires to distribute and retrieve the questionnaires via Weibo, Tencent QQ, WeChat online social media to consumers who like, share or share with Huawei social media.…”
Section: Sample and Proceduresmentioning
confidence: 99%